A 10 C’s of social networking, interconnections and the impact on social networking - Dar, Humaira; Shah, Asadullah (2013)
In this paper we provide some insights of 10 C's of Social Networking (SNg) which is an extension of so far reported 6 C's. These C's are Community, Connection, Communication, Collaboration, Common experience, Creativity, Coaching, Competition, Content, and finally Commerce or Social commerce. All these 10 C's are one way or another are related as chain of activities with each other. For example, Community is one of the fundamental concepts of SNs, Connection, Communication and Collaboration are inherently embedded with groups. This paper deeply elaborates upon all 10 C's. This paper provides a detailed analysis of 10 C's of SNs. These C's inherit meaningful insights between operational connectivity among users of SNg.